Invasive Detection of Coronary Microvascular Dysfunction: How It Began, and Where We Are Now - Samer Fawaz; Sarosh Khan; Rupert Simpson; Gerald Clesham; Christopher M Cook; John R Davies; Grigoris Karamasis; Thomas R Keeble (Interventional Cardiology: Reviews, Research, Resources, 2023)
The landscape of interventional cardiology is ever evolving. Contemporary practice has shifted from a stenosis-centred approach to the total characterisation of both the epicardial and microcirculatory vessels. Microcirculatory dysfunction plays an important role in the pathophysiology of acute and chronic coronary syndromes, and characterisation of the microcirculation has important clinical consequences. Accordingly, the invasive diagnosis of microcirculatory dysfunction is becoming a key feature of the interventional cardiologist’s toolkit. This review focuses on the methodology underpinning the invasive diagnosis of microvascular dysfunction and highlights the indices that have arisen from these methodologies.